Lifestyle challenges and mental health of professional tennis players: an exploratory case study - Shrom, S. J.; Cumming, J.; Fenton, S.-J. (International Journal of Sport and Exercise Psychology, 2022)
The professional tennis tour lifestyle has become increasingly difficult over time. Although the financial strain of tour life has been identified [International Tennis Federation. (2017, March 30). ITF pro circuit review. https://www.itftennis.com/procircuit/about-pro-circuit/player-pathway.aspx], there is a gap in our understanding of the additional lifestyle challenges that professional players face and the potential impact these have on their progression and mental health. Adopting an exploratory case study methodology [Yin, R. K. (2017). Case study research and applications: Design and methods. Sage.], with "Behind the Racquet", a social media platform aimed at raising awareness of professional players` challenges as its case, and theoretically underpinned by [Maslow, A. H. (1943). A theory of human motivation. Psychological Review, 50(4), 370-396.] hierarchy of needs, this study aimed to gain a contextual understanding of these challenges. Using "Behind the Racquet" as the data source provided a unique opportunity to gain authentic, self-reported experiences from a hard-to-reach population. The sample consisted of 65 professional players (33 males, 32 females; age range = 18-46 years; mean age = 27.34 years) from 28 different countries. Players achieved varying levels of success, including being Grand Slam and Olympic champions, ATP, and WTA Top 10 players, and within and outside of the world`s Top 100. Findings illustrated physical and mental fatigue, financial imbalance of the professional system, the social and psychological impact of living a nomadic existence, the weight of expectation, structural-caused instability, and mental illness as key challenges that players experience on the professional tour. These challenges, which inhibit players` ability to meet basic needs on each level of [Maslow, A. H. (1943). A theory of human motivation. Psychological Review, 50(4), 370-396.] hierarchy of needs, pose concerns to both players` progression on tour and their mental health.